2010
DOI: 10.1002/clc.20602
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disordered Breathing is Associated with Appropriate Implantable Cardioverter Defibrillator Therapy in Congestive Heart Failure Patients

Abstract: Background: Implantable cardioverter defibrillators (ICDs) are increasingly employed in patients affected by congestive heart failure (CHF) and sleep disordered breathing (SDB) is frequent in this population. Hypothesis: To investigate SDB prevalence and influence on appropriate ICD discharges in CHF patients. Methods: A total of 22 consecutive ICD patients with systolic CHF (left ventricular ejection fraction [LVEF]<45%) were studied by polysomnography. Results: A total of 17 (77.2%) showed SDB (apnea-hypopne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…The prevalence rate of OSA in our sample (40.5%) is consistent with previous findings in the literature (40–77%; Fries et al, 1999; Grimm et al, 2013; Mehra et al, 2006; Serizawa et al, 2008; Tomaello et al, 2010), although our rate of OSA and comorbid insomnia (11.9%) is low relative to previously reports in ICD patients with nocturnal ventricular arrhythmias (22–54.9%; Al-Jawder & Bahammam, 2011). Our prevalence rate for insomnia within the sample (28.6%) is lower but somewhat comparable to previous findings in heart failure patients (44%; Taylor et al, 2007), and suggests that insomnia is a considerable problem with these patients as a less-recognized and/or treated condition that until recently has received little attention (Cross et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence rate of OSA in our sample (40.5%) is consistent with previous findings in the literature (40–77%; Fries et al, 1999; Grimm et al, 2013; Mehra et al, 2006; Serizawa et al, 2008; Tomaello et al, 2010), although our rate of OSA and comorbid insomnia (11.9%) is low relative to previously reports in ICD patients with nocturnal ventricular arrhythmias (22–54.9%; Al-Jawder & Bahammam, 2011). Our prevalence rate for insomnia within the sample (28.6%) is lower but somewhat comparable to previous findings in heart failure patients (44%; Taylor et al, 2007), and suggests that insomnia is a considerable problem with these patients as a less-recognized and/or treated condition that until recently has received little attention (Cross et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The identification of an under-recognized condition, such as insomnia, could warrant the inclusion of psychological and/or hypnotic therapy to the constellation of medical care ICD patients receive which could substantially improve their cardiovascular functioning and/or quality of life. Apnea, whether alone or comorbid with insomnia, is particularly problematic for ICD patients as the aggregate cardiovascular effects of apnea (Kasai & Bradley, 2011) have been associated with arrhythmia and subsequent ICD discharge (Fichter et al, 2002; Serizawa et al, 2008; Tomaello et al, 2010). The finding that insomnia and apnea have the potential to co-occur suggests that concurrent psychological treatment for insomnia and respiratory therapy (i.e., continuous positive airway pressure [CPAP], the gold standard treatment for sleep apnea) in this population may be indicated; previous research demonstrates both the cardiovascular and psychological benefit of this dual approach (Abe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies reported SDB without differentiating subtypes. 13, 1719 Three studies reported OSA and CSA separately. 12, 14, 16 Two studies included patients with only CSA.…”
Section: Resultsmentioning
confidence: 99%
“…In a small cohort, Tomaello et al found a higher number of ICD therapies in CHF patients with concomitant SDB. 75 In 255 patients screened for SDB 6 months after implantation of a cardiac resynchronization device with defibrillator, we found an independent association between SDB and appropriate defibrillator therapies during a 48-month follow-up period (Fig. 2).…”
Section: Ventricular Tachycardiamentioning
confidence: 82%